OPTIMALISASI MANAJEMEN KEUANGAN UNTUK PENDIDIKAN DASAR YANG BERKUALITAS - Fauziah, Zuliani; Nur Cahyani, Bela Dwi; Fhadlilla Fharhah, Syilla; Rohman, Nur (Journal of Professional Elementary Education, 2024)
This study explores financial management at SDN 7 Lebak to support quality elementary education. Data were collected through direct observation and interviews with the treasurer, grade 5 teachers, and the principal using a qualitative approach. The results showed that the school's financial planning was well designed, with BOS funds allocated for teaching resources, facility improvements, and operational needs. However, there were problems with financial reporting through the Dapodik system, and there were no technological resources needed for digital-based assessments. Due to the absence of a public financial information board, transparency remains an issue. Joint budgeting with teachers improves fund allocation and stakeholder ownership. To meet the demands of contemporary education, increased financial management capacity, verified funding sources, and innovation in budget management are needed. This study underscores the importance of collective efforts by schools, government, and communities to achieve effective financial management of elementary education.